Book review: De Fremery, Wayne. Cats, carpenters, and accountants: bibliographical foundations of information science - Elena Maceviciute (Information Research: An International Electronic Journal)
De Fremery, Wayne. (2024). Cats, carpenters, and accountants: bibliographical foundations of information science. Cambridge, Mas.: The MIT Press. xiv, 279 p. ISBN 978-0-262-54759-8